Integrated Model of Palliative Care in the Emergency Department - Rosenberg, Mark (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2013)
An integrated model of palliative care in the emergency department (ED) of an inner city academic teaching center utilized existing hospital resources to reduce hospital length of stay (LOS) and reduce overall cost. Benefits related to resuscitation rates, intensity of care, and patient satisfaction are attributed to the ED-based palliative team’s ability to provide real time consults, and utilize InterQual criteria to admit to a less costly level of care or transfer directly to home or hospice.